2022
DOI: 10.1021/jacs.2c07064
|View full text |Cite
|
Sign up to set email alerts
|

Structural Disorder as the Origin of Optical Properties and Spectral Dynamics in Squaraine Nano-Aggregates

Abstract: In contrast to regular J-and H-aggregates, thin film squaraine aggregates usually have broad absorption spectra containing both J-and H-like features, which are favorable for organic photovoltaics. Despite being successfully applied in organic photovoltaics for years, a clear interpretation of these optical properties by relating them to specific excited states and an underlying aggregate structure has not been made. In this work, by static and transient absorption spectroscopy on aggregated n-butyl anilino sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…This suggested that these two molecules exhibit an excited-state interaction only in their aggregated state. The SQR molecules exhibited emission at 658 nm in the THF solution (Figure S1, olive), but this emission completely disappeared in the case of SQR aggregates (Figure C, olive) and QTH-SQR aggregates (Figure C, blue), indicating the purely dark lower-energy states in SQR aggregates …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that these two molecules exhibit an excited-state interaction only in their aggregated state. The SQR molecules exhibited emission at 658 nm in the THF solution (Figure S1, olive), but this emission completely disappeared in the case of SQR aggregates (Figure C, olive) and QTH-SQR aggregates (Figure C, blue), indicating the purely dark lower-energy states in SQR aggregates …”
Section: Resultsmentioning
confidence: 99%
“…Squaraine (SQR) dyes exhibit several advantageous properties including strong absorption in the visible to NIR region, high molar extinction coefficients, and good photostability compared to traditional cyanine dyes due to their unique rigid and planar structure . In addition, they easily form aggregates via strong intermolecular interactions due to their quadrupolar structure . Therefore, they find potential in photovoltaic and biomedical applications. , They contain a four-membered electron-deficient ring, which acts as an electron acceptor. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…73,74,[78][79][80][81][82][83][84][85] Finally, we mention that the structures are sensitive to the environments, such as presence of other ligands, 86 and aggregation. [87][88][89][90][91][92][93][94][95][96][97] The suitability of these molecules in the application of solar cells and compatibility with the acceptors 84,[98][99][100][101][102][103][104][105][106] for electron transport will need detailed electronic properties, which are discussed below.…”
Section: Scheme 2 the Synthesis Of Cis Indoline Structure Scheme 3 St...mentioning
confidence: 99%
“…The influence of the replacement of different elements such as carbon, oxygen and germanium with silicon were also investigated to understand effect of different Furthermore, we also investigated the aggregation effect of the silicon analog of fluorescein since dye aggregation is very commonly observed in many fluorescein and rhodamine derivatives [81][82][83][84][85] and important in organic small molecule materials. [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] Most dyes can be shown to produce the spectrum of the unassociated dye for sufficiently diluted solutions. The spectral changes observed upon increasing concentrations have been attributed to dye association in the form of either parallel or head-to-tail manner.…”
Section: Introductionmentioning
confidence: 99%